2016
DOI: 10.4103/1119-3077.180049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of routine preoperative fasting on residual gastric volume and acid in patients undergoing myomectomy

Abstract: Preoperative carbohydrate or water intake up to 2 h before surgery is safe with better satisfaction when compared to overnight fasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Prolonged fasting (i.e. nil per os after midnight) has not been shown to lower the amount of gastric contents nor decrease gastric acidity (10,13,14). Perioperative fasting is associated with increased surgical stress, increased insulin resistance and impaired gastrointestinal function (6,7,15).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged fasting (i.e. nil per os after midnight) has not been shown to lower the amount of gastric contents nor decrease gastric acidity (10,13,14). Perioperative fasting is associated with increased surgical stress, increased insulin resistance and impaired gastrointestinal function (6,7,15).…”
Section: Discussionmentioning
confidence: 99%
“…Many published studies have reported no association between fasting duration and adverse events such as vomiting and pulmonary aspiration [16][17][18] . Schmitz and Ajuzieogu reported that gastric content volume did not correlate with fasting times in children and adolescents [19][20] . This evidence questions the necessity of pre-sedation fasting.…”
Section: Choice Of Sedativesmentioning
confidence: 96%
“…The 20 studies identified by our search regarding clear liquids intake and gastric volumes did not report any event of aspiration or regurgitation. [ 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 ] The studies were of Low, or Very Low level of evidence. In eight studies, after overnight fasting, one group received water to consume medications and the other, received between 100 and 500 mL water till 2 hours before induction of anaesthesia.…”
Section: Adult Sectionmentioning
confidence: 99%
“…In eight studies, after overnight fasting, one group received water to consume medications and the other, received between 100 and 500 mL water till 2 hours before induction of anaesthesia. [ 65 66 67 68 69 70 71 72 ]…”
Section: Adult Sectionmentioning
confidence: 99%